Comprehensive diastolic exercise stress echocardiography in heart failure with preserved ejection fraction. (14th October 2021) - Varga, A; Peteiro, J; Ciampi, Q; Rodriguez-Zanella, H; Simova, I; Zagatina, A; Arbucci, R; Celutkiene, J; Camarozano, A.C; Agoston, G; D Andrea, A; Merli, E; et al.
Abstract: Background: In heart failure with preserved ejection fraction (HFpEF), diastolic exercise stress echocardiography (ESE) is currently recommended with E/e' and systolic pulmonary artery pressure (SPAP) from tricuspid regurgitant jet velocity (TRV). Purpose: To evaluate conventional and advanced ESE parameters in patients with HFpEF. Methods: We prospectively screened 124 patients with suspected HFpEF (dyspnea, resting EF >50%, increased natriuretic peptide levels) and HFA-PEFF score ≥1. Of these 124, 10 patients were excluded for history of coronary artery disease, 3 for severe mitral regurgitation (MR), 12 for inducible ischemia. The final study population consisted of 99 patients (mean age 63±7 yrs, 57 females). All underwent ESE, with semi-supine bike (n=35), upright bike (n=20) or treadmill (n=44 patients) in 11 accredited labs from 9 countries (Argentina, Brazil, Bulgaria, Hungary, Italy, Lithuania, Mexico, Russia and Spain). In addition to E/e' average (abnormal stress response ≥15 units) and TRV (abnormal stress response >3.4 m/s), we measured 8 additional criteria: B-lines (4-site simplified scan, abnormal stress value ≥2); cardiac index (CI) reserve (increase from rest to stress, abnormal <1.63 l/min/m 2 ), ejection fraction (EF, abnormal increase <5%), global longitudinal strain (GLS, abnormal increase <2%), end-diastolic volume (EDV, abnormal stress < rest); heart rate reserve (HRR, abnormal <1.80); left atrial volume index, (LAVI, abnormal increase >6.8 ml/m 2 ); MR (abnormal, stress value more than mild). Results: Technical success rate during stress ranged from 100% for B-lines to 75% for GLS: see Table. At individual criteria analysis, positivity rate in interpretable studies ranged from 67% of HRR to 10% of peak MR: see table. At individual patient analysis, an abnormal response in 1 ESE criterion occurred in 4 pts (4%), of 2 to 4 criteria in 71 pts (72%) and of ≥5 criteria in 24 (24%). Conclusion: In suspected HFpEF, ESE is helpful in the screening phase to identify extra-diastolic causes of dyspnea such as myocardial ischemia or severe MR. In the diagnostic phase, a comprehensive ESE captures the functional heterogeneity of HFpEF, with variable association of multiple phenotypes, the most frequent represented by reduced chronotropic, cardiac or contractile reserve and pulmonary congestion. Funding Acknowledgement: Type of funding sources: None.